Keep it simple, not stupid: How to save the EU fiscal framework? - Kuusi Tero; Puonti Päivi (The Research Institute of the Finnish Economy (ETLA), 2022)
In this paper, we describe key problems of the current EU's fiscal framework and offer constructive options for its reform. A comprehensive reassessment of the rules is necessary, as the development of the rules has reached an impasse for both political and technical reasons. In our view, Europe needs fiscal rules to ensure the sustainability of public finances. In order to reconcile the freedom and responsibility of member states' fiscal policies, a balance must be struck in which the rules are simple enough to facilitate monitoring of compliance yet effective enough to mean that the need for cross-country bail-out measures is sufficiently rare. Our conclusion is that the new rules should emphasise the long-term debt sustainability target more clearly, while at the same time making its monitoring more effective through better short-term indicators, in particular the expenditure benchmark. We provide a proposal for a practical implementation option which is largely consistent with the current rules. At the same time, the expenditure benchmark should be reformed in order to further its countercyclical impact on fiscal policy, and it should replace the structural balance as the operational indicator of fiscal policy stance. Responsibility for economic policy decisions and their consequences should be fully restored to the Member States and the role of national supervisory bodies should be strengthened. Cross-country bail-out measures in times of crisis should be accompanied by strict conditionality that, in good times, the fiscal policy must be in line with the reformed EU framework.
Keywords: E61; E62; H60; H63; 330; Fiscal policy; EU; Fiscal rules; Public debt; Fiscal stance